2013
DOI: 10.1038/bmt.2013.118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of palifermin on intestinal mucositis of HSCT recipients after BEAM

Abstract: The matched-control study failed to show a clinical relevant impact of palifermin on intestinal mucositis, although there was a reduced inflammatory response and less febrile neutropenia among patients who had no bacteraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…Not surprisingly, preserving the mucosal barrier by using less mucotoxic non-myeloablative conditioning regimens and drugs, including rh-KGF and Wnt signalling agonist R-spondin-1, has been shown to ameliorate or delay acute GVHD, although thus far only in animal studies (Panoskaltsis-Mortari et al, 1998;Takashima et al, 2011). In humans, rh-KGF seemed not to be protective for GVHD, despite the reduced incidence of oral mucositis, but this is probably explained by a virtual lack of effect of the growth factor on intestinal mucositis (Langner et al, 2008;Herbers et al, 2014b).…”
Section: Clinical Consequences Of Mbimentioning
confidence: 99%
“…Not surprisingly, preserving the mucosal barrier by using less mucotoxic non-myeloablative conditioning regimens and drugs, including rh-KGF and Wnt signalling agonist R-spondin-1, has been shown to ameliorate or delay acute GVHD, although thus far only in animal studies (Panoskaltsis-Mortari et al, 1998;Takashima et al, 2011). In humans, rh-KGF seemed not to be protective for GVHD, despite the reduced incidence of oral mucositis, but this is probably explained by a virtual lack of effect of the growth factor on intestinal mucositis (Langner et al, 2008;Herbers et al, 2014b).…”
Section: Clinical Consequences Of Mbimentioning
confidence: 99%
“…[6][7][8] These discrepancies may depend on the type of conditioning used. The importance of conditioning is suggested, in fact, by studies from Herbers et al who reported that palifermin administration in patients treated using a BEAM conditioning schedule leads to a reduction in the rate of some infections such as 'fever of unknown origin' (FUO), 9 while the same group did not find this effect in patients treated with high-dose melphalan (HD-PAM). 10 In a previous work we indeed found that conditioning significantly interacts with the effects of palifermin and that this agent is able to reduce the rate of severe mucositis only after conditioning based on BEAM or on BU/Thiothepa treatment but not after 'HD-PAM' conditioning.…”
Section: Introductionmentioning
confidence: 94%
“…These observations are fully in keeping with the data reported by Herberts on reduction of the FUO rate after paliferminin patients were treated by BEAM. 9 How can a prophylactic agent be more active based on type of conditioning? This could be due to differences in the toxicity of different drugs used in high-dose chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions aimed at attenuating proinflammatory cytokines or stimulating anti-inflammatory cytokines may offer a way to prevent toxicities [120, 121, 127131]. …”
Section: Mucosal Injurymentioning
confidence: 99%